Implementasi Sukuk Sebagai Instrumen Keuangan Syariah Dalam Pembangunan Infrastruktur - Indah Permata Sari; Hayifah Sasi Firmadi (DPPM Universitas Pelita Bangsa, 2025)
This study aims to explore and analyze the implementation strategy of sukuk as a sharia financial instrument that can support sustainable infrastructure development in Indonesia. Specifically, this study aims to identify how sukuk can function as an effective and efficient source of financing, as well as understand the obstacles faced in its implementation, including regulatory aspects and public understanding. The method used in this study is a qualitative approach with secondary data collection through literature studies, which include scientific journals, policy reports, and related official documents. The results of the study indicate that sukuk has great potential to increase transparent and accountable fund allocation, as well as accelerate infrastructure development. However, obstacles such as lack of public understanding and suboptimal regulations are still significant challenges. This study recommends the need to increase sharia financial literacy and improve regulations so that sukuk can be implemented more effectively in supporting infrastructure development in Indonesia.